FREQUENCY OF PORT SITE WOUND INFECTION AFTER GALL BLADDER REMOVAL WITH AND WITHOUT RETRIEVAL BAG IN LAPAROSCOPIC CHOLECYSTECTOMY - ANWAR , MR; LUND , MA; BHATTI , MA (Biological and Clinical Sciences Research Journal, 2024)
Cholecystectomy is the preferred therapy for symptomatic gallstones, which involves removing the organ implicated in the development of gallstones and the difficulties that arise from them. This research was conducted to examine the incidence of port site infection between patients having laparoscopic cholecystectomy with and without retrieval bags. Objective: To compare the frequency of port site wound infection after gall bladder removal with and without retrieval bag in laparoscopic cholecystectomy. Methods: This Randomized Controlled Trial was carried out at the General Surgical Department of Allama Iqbal Teaching Hospital, Dera Ghazi Khan. The study duration was six months, from June 2022 to December 2022. One hundred patients in total were recruited and divided into two groups. In Group A, after a laparoscopic cholecystectomy, the laparoscope was inserted via the epigastric port site, and a retrieval bag was used to insert the bag through the umbilical port site. The laparoscope was moved to the epigastric port in Group B, where the gall bladder was removed without a retrieval bag. Patients in this group were monitored for a month to look for post-operative port site infections. Results: In the current study, 100 cases were enrolled. Of the male patients, 44 (44%) and 56 (56%) were female. The mean age of our study cases was 31.77 ± 2.86 years. Of these 100 study cases, 33 (33%) had ASA grade I, and 67 (67%) had ASA grade II. Port site infection was present in 7(7%) of our study cases. Port site infection in group A was present in 4 %, while in group B was 10 %. (p = 0.436). Conclusion: Laparoscopic cholecystectomy using a retrieval bag for removal of the gallbladder is “quite safe, reliable and effective procedure” as the frequency of port site infection was low in our study cases. Port site infection was more frequent in patients undergoing laparoscopic cholecystectomy without retrieval bags as compared with those with retrieval bags. However, this difference was not statistically significant.